2007
DOI: 10.1161/circresaha.107.152975
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pathways for Atherosclerosis in Mice

Abstract: Abstract-We report a combined genetic and genomic analysis of atherosclerosis in a cross between the strains C3H/HeJ and C57BL/6J on a hyperlipidemic apolipoprotein E-null background. We incorporated sex and sex-by-genotype interactions into our model selection procedure to identify 10 quantitative trait loci for lesion size, revealing a level of complexity greater than previously thought. Of the known risk factors for atherosclerosis, plasma triglyceride levels and plasma glucose to insulin ratios were partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 62 publications
3
76
1
Order By: Relevance
“…The BxH Apoe -/-cross was constructed using 2 strains of mice that differ dramatically in lesion susceptibility: C3H (resistant) and B6 (susceptible). The mean lesion size in F2 females was 244,524 ± 8,694 μm 2 , whereas the mean for F2 males was 176,424 ± 7,220 μm 2 (P < 1 × 10 -4 , Student's t test) (10). By integrating genotype, gene expression, and aortic lesion size measured in 334 F2 mice and testing causal, reactive, and independent models using the LCMS procedure, we identified 292 genes supported as causal for aortic lesions at a false discovery rate (FDR) of less than 5%.…”
Section: Identification Of Genes Testing Causal For Aortic Lesions Inmentioning
confidence: 87%
See 1 more Smart Citation
“…The BxH Apoe -/-cross was constructed using 2 strains of mice that differ dramatically in lesion susceptibility: C3H (resistant) and B6 (susceptible). The mean lesion size in F2 females was 244,524 ± 8,694 μm 2 , whereas the mean for F2 males was 176,424 ± 7,220 μm 2 (P < 1 × 10 -4 , Student's t test) (10). By integrating genotype, gene expression, and aortic lesion size measured in 334 F2 mice and testing causal, reactive, and independent models using the LCMS procedure, we identified 292 genes supported as causal for aortic lesions at a false discovery rate (FDR) of less than 5%.…”
Section: Identification Of Genes Testing Causal For Aortic Lesions Inmentioning
confidence: 87%
“…10,11). We identified 292 genes that were supported as causal for aortic lesions from the adipose and liver of this cross.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of the arterial wall of the two strains focused on one or a few genes of interest (13,14), thus severely narrowing the scope of the findings. Due to the polygenic nature of atherosclerosis, recent studies have taken advantage of the microarray technology to examine genome-wide gene expression differences between the strains (18,20). The genome-wide transcriptional profiling of aortas from wild-type B6 and C3H mice identified a list of candidate genes relevant to growth, differentiation, inflammation, cathecholamine synthesis, phosphatase activity, peroxisome function, insulin-like growth factor activity, and antigen presentation (18).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, apoE Ϫ/Ϫ mice develop lesions that are similar in many aspects to human lesions (7). In an intercross derived from B6.apoE Ϫ/Ϫ and C3H.apoE Ϫ/Ϫ parental strains, Wang et al (20) performed expression array analysis of the liver and adipose tissues and identified Ͼ 10,000 expression quantitative trait loci. However, the vessel wall, a tissue most relevant to atherosclerosis, had not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…For this, we repeatedly crossed the mutation, originally on a mixed C57BL/6JxC3HeB/FeJ background, to inbred C57BL/6J mice. We felt this was important as C3H mice are highly resistant to atherosclerosis and nearly a dozen major loci contribute to the differences in susceptibility between C57BL/6 and C3H mice on an apoE null background ( 18 ). After 10 generations of backcrossing, we intercrossed heterozygous mice.…”
Section: Dose-dependent Effects Of An Csf-1 Defi Ciency In a Defi Nedmentioning
confidence: 99%